2021
DOI: 10.1080/02813432.2021.1908715
|View full text |Cite
|
Sign up to set email alerts
|

Phone triage nurses’ assessment of respiratory tract infections – the tightrope walk between gatekeeping and service providing. A qualitative study

Abstract: Background: Phone nurses triage callers to Norwegian out-of-hours cooperatives to estimate the appropriate urgency and level of care for the caller. Many callers with mild symptoms of respiratory tract infections receive a doctor's consultation, which may lead to busy sessions and in turn impair clinical decisions. Objective: This study explores how phone triage nurses assess callers with mild-to-moderate symptoms of respiratory tract infections and their views and experiences on triaging and counselling these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…Four were small UK-based, mixed-methods studies with qualitative components, published between 2011 and 2019; two reported experiences of ANPs conducting home visits in Bristol and Cumbria; 11 , 19 one reported a pilot of integrating US-trained PAs into an OOH service in Scotland; 30 and one reported the evaluation of a programme to train paramedics to work in OOH in Bristol. 31 One study in Norway investigated the experiences of nurses triaging patients presenting with respiratory symptoms, 32 and one study in the Netherlands explored the views of GPs and nurse practitioners (NPs) taking part in a quasi-experimental study into optimal skill mix in OOH primary care. 33 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four were small UK-based, mixed-methods studies with qualitative components, published between 2011 and 2019; two reported experiences of ANPs conducting home visits in Bristol and Cumbria; 11 , 19 one reported a pilot of integrating US-trained PAs into an OOH service in Scotland; 30 and one reported the evaluation of a programme to train paramedics to work in OOH in Bristol. 31 One study in Norway investigated the experiences of nurses triaging patients presenting with respiratory symptoms, 32 and one study in the Netherlands explored the views of GPs and nurse practitioners (NPs) taking part in a quasi-experimental study into optimal skill mix in OOH primary care. 33 …”
Section: Resultsmentioning
confidence: 99%
“…Nurses conducting telephone triage reported offering GP appointments to some patients who didn’t need them, because they were worried about missing serious illness, and lacked the confidence to reassure patients and their parents over the phone. 32 This led to both slower triage (as the nurses felt the need to document the history in detail) and excessive numbers of GP appointments:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telephone triage has the potential to reduce the workload of GPs [ 9 ]. Nevertheless, telephone triage nurses are reluctant to call themselves gatekeepers to the out-of-hours GP cooperatives [ 15 ]. They rather describe themselves as service providers who want to reach a consensus with the caller about the right level of care.…”
Section: Introductionmentioning
confidence: 99%
“…Travelhet er heller ikke kvalitetsdrivende, verken på kort eller lang sikt. Studier fra norsk legevaktsammenheng viste at travelhet blant sykepleierne som prioriterer og hastevurderer pasientene på telefon fører til større forbruk legevakt (Lindberg, Rebnord, & Høye, 2021) og at legenes foreskriving av antibiotika forholdsmessig gikk opp når det var travelt på legevaktene (Lindberg, Gjelstad, Foshaug, & Høye, 2017). Tilstrekkelig tid og rammer til å gjøre jobben grundig fremmer kontinuitet og kvalitet, og er muligens også økonomisk besparende for virksomhetene på sikt.…”
unclassified